SOCIAL AND ENVIRONMENTAL INJUSTICE IN MORTAL ENGINES (2018) FILM: A STUDY OF POSTCOLONIAL ECOCRITICISM - Saputra, Muhamad Ramadan; Chusna, Inayatul (Sanata Dharma University, 2024)
This research aims to uncover the social and environmental issues depicted in Mortal Engines (2018) and explore the possible implications the film promotes from the disparitys depiction concerning social and environmental justice. The study utilizes Huggan and Tiffin's Postcolonial ecocriticism and mise-en-scene theory, employing a descriptive-qualitative research method. The data is collected from the characters' dialogue and visual representations highlighting social and environmental injustice. The findings show that: 1) There are significant correlations and interconnectedness between different issues, resulting in social and environmental injustice within the film; 2) This injustice originates from ecological imperialism and is perpetuated by dualistic and binary thinking. These thinking patterns lead to bio-colonization, violence, abuse of power, marginalization, othering, and exploitation, contributing to power imbalances, social injustice, environmental racism, and degradation; 3) The depiction employs mise-en-scene, dialogue, symbols, allegory, visual language, and literary devices, the film effectively engages the audience and promotes social and environmental justice values; 4) The research also uncovers the film's role as an interventionist and counter-hegemony, advocating for social and environmental justice, decolonization, resistance, sustainability, humanity, and historicism.